Aplikasi Committee Recruitment Broadcast di Universitas Kristen Petra Berbasis Website dan Facebook API - Wijaya, Caroline Indah; Handojo, Andreas; Purbowo, Anita Nathania (Jurnal Infra, 2015)
Dissemination of information and recruitment of event committees at Petra Christian University are still manually performed. Students still have difficulties to get the information about activities / events in campus which are still open committee recruitment. Therefore, Petra Christian University needs a website to provide information to all students and facilitate students in registering committee activities.This thesis made web-based application inside social media facebook which use facebook API and PostageApp email service to broadcast committee informations. Features provided in this application are adding new committee activities, searching activities, the registration of committee, committee acceptance, notification, the committee appraisal, displaying the committee history of students, approving the committee activities, and importing data from an excel file. This application is made using the programming language PHP and HTML, CodeIgniter framework, and MySQL database.Based on the tests performed, this website application can be run on facebook canvas that can be accessed after logging on facebook and approving the permissions dialog. This application can help students get information about the activities of the committee at Petra Christian University, assist the process of registration and recruitment committee. The website can also provide broadcast facebook and email notifications to students. This application derive satisfaction score of 82,03% respondents.